2019
DOI: 10.3390/f10030251
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotopes of Riparian Forests Trees in the Savannas of the Volta Sub-Basin of Ghana Reveal Contrasting Responses to Climatic and Environmental Variations

Abstract: Stable isotopes of tree rings are frequently used as proxies in climate change studies. However, species-specific relationships between climate and tree-ring stable isotopes have not yet been studied in riparian forests in the savannas of West Africa. Four cross-dated discs, each of Afzelia africana Sm. (evergreen) and Anogeissus leiocarpus (DC.) Guill. & Perr. (deciduous) in the humid (HSZ) and dry (DSZ) savanna zones of the Volta basin in Ghana were selected from a larger tree-ring dataset to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Comparatively, the dry season of the forest zone is more defined than the evergreen forest types. The mean annual rainfall ranges from 800 to 2800 mm/year and that of temperature is 26.4 °C in the forest zones [ 13 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Comparatively, the dry season of the forest zone is more defined than the evergreen forest types. The mean annual rainfall ranges from 800 to 2800 mm/year and that of temperature is 26.4 °C in the forest zones [ 13 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dendrochronology, which uses tree rings as a tool of retrospective bioindication, allows users to obtain information on the growth rates of trees, past climate conditions, and the dynamics and carbon sequestration rates of natural forest stands (Gebrekirstos et al 2014). The carbon isotope composition of riparian trees can be used to reconstruct climate variability and assess ecological responses to climate change, as shown for the Volta Region of Ghana (Boakye et al 2019). The periodicity of tree growth ring formation in seasonally flooded peatlands in Borneo, Indonesia, was studied by Worbes et al (2017).…”
Section: Impacts Of Climate Change On Trees and Forest Ecosystemsmentioning
confidence: 99%
“…Although riparian forests are frequently studied in sub‐Saharan tropical Africa, much less information is available on their biogeography, particularly in mountain areas. Previous studies were conducted in South Africa (Hood & Naiman, 2000), Benin (Natta, 2003), Togo (Adjossou, 2004; Kokou et al, 2008), Central Africa (Gautier‐Hion & Brugiere, 2005), the Volta Sub‐Basin of Ghana (Boakye et al, 2019), Southern Sierra Leone (Fayiah et al, 2020), and South East Kenya (Habel & Ulrich, 2021) have shown that riparian areas are generally richer than other forest ecosystems. However, the floristic similarity between riparian and “Terre firme” forests has not been investigated to estimate the proportion of regional humid relict species in riparian forests, thus allowing the discussion of their status as forest refugia.…”
Section: Introductionmentioning
confidence: 99%